The Impact of Orthography on Text Production in Three Languages: Catalan, English, and Spanish - Llaurado, Anna; Dockrell, Julie E. (Frontiers in Psychology, 2020)
Learning to write effectively is key for learning and for wider participation in social communities. In English, transcription skills (handwriting and spelling) constrain written production at the early stages of writing. The effect of transcription diminishes with age and reading skills impact text production. Less is known about how transcription and reading interact with writing in other languages and writing systems. In this study, we explore the relationships between spelling, reading and the length and quality of written text production in primary school children speaking three different languages: Catalan, English and Spanish. Languages that contrast orthographically and morphologically. Language had a significant effect on text production measures: Young Spanish children produced longer texts which were of higher quality than the other two cohorts. We examined if the characteristics of the writing system and the morphological system of each language had an impact on the text level spelling. The Spanish children produced the lowest number of spelling errors both at the root and for inflectional morphemes whereas the English produced the highest number of both. The Catalan children did not differ significantly from their English peers at the root level spelling but did at the morphological level. To test how transcription and reading skills impact on text production skills, we conducted regression analysis to test a three step model (age, transcription and reading skills) for each language. Different patterns of relationships between transcription, reading and text production emerged. In English and Catalan text productivity and quality were explained by age and transcription skills whereas in Spanish the text quality was explained by the child’s reading skills. Implications for developmental models of writing development are discussed.